2015
DOI: 10.1016/j.schres.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive course in first-episode psychosis and clinical correlates: A 4 year longitudinal study using the MATRICS Consensus Cognitive Battery

Abstract: While cognitive impairments are prevalent in first-episode psychosis, the course of these deficits is not fully understood. Most deficits appear to remain stable, however there is uncertainty regarding the trajectory of specific cognitive domains after illness onset. This study investigates the longitudinal course of cognitive deficits four years after a first-episode of psychosis and the relationship of performance with clinical course and response to treatment.Twenty three individuals with psychotic illness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
(46 reference statements)
2
16
0
Order By: Relevance
“…Thirty-five participants between 18 and 60 years of age were recruited from the local community as part of the Galway Bipolar Study (Emsell, Leemans, et al 2013;Emsell, Langan, et al 2013). An additional seven individuals with remitted BD participated in a follow-up imaging of a first episode psychosis study and underwent an identical scanning procedure were included in connectivity analysis (Scanlon et al 2014;Kenney et al 2015). We recruited 43 age and gender matched healthy volunteers from the local community.…”
Section: Participantsmentioning
confidence: 99%
“…Thirty-five participants between 18 and 60 years of age were recruited from the local community as part of the Galway Bipolar Study (Emsell, Leemans, et al 2013;Emsell, Langan, et al 2013). An additional seven individuals with remitted BD participated in a follow-up imaging of a first episode psychosis study and underwent an identical scanning procedure were included in connectivity analysis (Scanlon et al 2014;Kenney et al 2015). We recruited 43 age and gender matched healthy volunteers from the local community.…”
Section: Participantsmentioning
confidence: 99%
“…The MATRICS initiative was launched to foster the development of a cognitive consensus battery for use in clinical trials 19,20. The MCCB battery has been translated into several languages, showing a high reliability and validity of the construct 19,3639. MCCB data show that CIRCuiTS participants improve significantly post-intervention on the neurocognitive composite score and on 4 on the 7 cognitive domains considered (Speed of Processing, Working Memory, Visual Learning and Verbal Learning).…”
Section: Discussionmentioning
confidence: 99%
“…The MCCB assesses 7 cognitive domains known to be impaired in schizophrenia [ 37 ]. Two cognitive tests from the battery, verbal learning (Hopkins Verbal Learning Test -Revised) and verbal fluency (Category fluency: Animal fluency) were used in the current analyses (see [ 3 ] for description of cognitive tests).…”
Section: Methods and Materials Participantsmentioning
confidence: 99%
“…Cognitive deficits are prevalent in early stages of psychosis, deficits of verbal cognition being the most consistent in the literature [ 1 ], which may also be susceptible to further deterioration longitudinally [ 2 ]. In a previous study, we identified verbal learning and verbal fluency to remain persistently impaired compared to other cognitive domains four years subsequent to a first episode of psychosis [ 3 ]. These verbal deficits have been linked to functional outcome [ 4 ] and positive symptoms of the disorder [ 5 , 6 ] and it is therefore vital to understand the precise neuroanatomical contributions of these cognitive impairments to assist in early diagnosis and targeted therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%